Intervention in the foreign exchange market, market turnover and the the impact on exchange and interest rate dynamics in the Caribbean - Seerattan, Dave ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Investigates in a multivariate GARCH framework the links between direct intervention, interest rate policy, exchange rates and trading volumes in the foreign exchange market. Looks at whether direct intervention signals the future interest rate policy stance of the central bank and are designed to 'lean against the wind' of exchange rate trends in select Caribbean countries.